Selected medical and social aspects of the Covid-19 pandemic - Cipora, Elżbieta; Mielnik, Aneta (Journal of Education, Health and Sport, 2021)
The Covid-19 pandemic poses a huge threat to human health and life as well as the socio-economic functioning. The aim of the study is to present selected medical and social aspects related to the Covid-19 pandemic. The research method used was a review and analysis of the literature from the PubMed database supplemented with epidemiological reports. The following keywords were used to search for publications: „Covid-19”, „medical aspects of Covid-19”, „social aspects of Covid-19”. The Covid-19 pandemic has destabilized public health worldwide and has had multiple negative social consequences. It was the cause of the global economic and economic crisis. Covid-19 has been described as a sudden adverse and multidimensional medical and social experience, the consequences of which are present and will be felt for many years to come. The epidemiological, health and economic situation of the society should be monitored and measures should be taken to reduce the severity of the negative effects of the Covid-19 pandemic.